2020
DOI: 10.1155/2020/4635163
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Mitigates Hippocampal Tau Acetylation and Cognitive Deficit by Activation SIRT1 in Aged Rats following Anesthesia and Surgery

Abstract: Postoperative cognitive dysfunction (POCD) is a sever postsurgical neurological complication in the elderly population. As the global acceleration of population ageing, POCD is proved to be a great challenge to the present labor market and healthcare system. In the present study, our findings showed that tau acetylation mediated by SIRT1 deficiency resulted in tau hyperphosphorylation in the hippocampus of the aged POCD model and consequently contributed to cognitive impairment. Interestingly, pretreatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…We observed a decreased SIRT1 expression in the hippocampus 1 and 3 days after anesthesia and surgery. Our results are in keeping with recent works [39,40]. SIRT1 is enriched in the nuclei and cytoplasm of microglia, implicating microglia as the target of SIRT1 in hippocampus.…”
Section: Discussionsupporting
confidence: 93%
“…We observed a decreased SIRT1 expression in the hippocampus 1 and 3 days after anesthesia and surgery. Our results are in keeping with recent works [39,40]. SIRT1 is enriched in the nuclei and cytoplasm of microglia, implicating microglia as the target of SIRT1 in hippocampus.…”
Section: Discussionsupporting
confidence: 93%
“… 140 Our study and other studies found that the reduction of SIRT1 was associated with postoperative cognitive impairment by activating the neuroinflammatory pathway and inhibiting neurotrophic factors. 141 , 142 Considering our previous findings that SIRT1 mediated abnormal tau modification in an aged POCD model, 143 it is plausible that SIRT1 is involved in sleep disturbance-related POCD. Future studies are needed to validate this hypothesis.…”
Section: Potential Mechanisms Underlying Perioperative Sleep Disturbance-associated Pocdmentioning
confidence: 98%
“…Postoperative cognitive dysfunction (POCD) is one of the most common postoperative complications in elderly patients ( Granger and Barnett, 2021 ) and is characterized by declines in learning, memory, attention, and executive capability following anesthesia and surgery ( Chen et al, 2019 ; Yan et al, 2020 ). Clinical evidence indicates that POCD may contribute to increased mortality, decreased quality of life, prolonged hospitalization, and increased burden on the medical care system ( Steinmetz et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%